Identification of a novel cell type in peripheral lymphoid organs of mice. V. Purification of spleen dendritic cells, new surface markers, and maintenance in vitro (The Rockefeller University Press, 1979)
Dendritic cells (DCs; 1) have been purified from mouse spleen in good yield. Spleen cell suspensions were floated on dense bovine plasma albumin (BPA) columns, and the low density fraction was adhered to glass (2). The adherent cells consisted of DCs and immature macrophages most of which eluted in a viable state from the culture dish after overnight incubation. The macrophages were then removed by selective rosetting with opsonized erythrocytes and recentrifugation on dense BPA. This protocol resulted in a purified DC fraction, containing 1--3 X 10(5) DCs/spleen, which was homogeneous and distinctive in its properties. All cells exhibited the phase contrast and transmission electron microscopy (EM) cytologic features that were previously described for freshly isolated adherent DCs. By scanning EM, most purified DCs exhibited a remarkable array of bulbous protrusions of varying length and shape, unlike any other lymphoid cell. All DCs expressed surface Ia and other major histocompatibility complex (MHC)- linked alloantigens. DCs, however, lacked surface Ig and T-cell antigens, and did not bind or interiorize opsonized erythrocytes. Purified DCs have been maintined in vitro for 3 days. Recovery of cultured purified cells was 70% or more of starting cell numbers. When [3H]uridine-tagged DCs were mixed with nonlabeled heterogeneous spleen cells, 70--80% of the labeled DCs were recovered as viable cells 2--3 days later. Purified DCs did not readhere to tissue culture surfaces and did not proliferate, even when cultured with mitogenic doses of concanavalin A and lipopolysaccharide. Finally, DCs did not change their cytologic or surface properties after 3 days of culture. These observations extend the evidence that DCs are a novel cell type and provide useful properties and techniques for their further study.